An agent‐based model of tourism destinations choice. (9th November 2018) - Alvarez, Emiliano; Brida, Juan Gabriel
Abstract: This study introduces a dynamic agent‐based model to represent the evolution of the choice of destinations by tourists. The model assumes that this choice depends on their personal tastes (characterized by their preferences for goods and services) and certain characteristics of other tourists (called crowding types), on the degree of inertia of the individuals and relevant information about the characteristics of visitors to other destinations. The model shows that the individual choices and the characterization of destinations are emergent properties of the system. The simulations show the formation of stable groups of individuals sharing destination, an endogenously increasing level of specialization of destinations, as well as an increasing market concentration, and that individuals of different characteristics can share destinations.